1997
DOI: 10.1007/bf02303744
|View full text |Cite
|
Sign up to set email alerts
|

Detection of recurrent and metastatic colorectal cancer: Comparison of positron emission tomography and computed tomography

Abstract: FDG-PET is more sensitive than CT in the clinical assessment of patients with recurrent or metastatic CRC, and provides an accurate means of selecting appropriate treatment for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(92 citation statements)
references
References 31 publications
2
81
1
8
Order By: Relevance
“…18 F-FDG PET/CT has been proven to be a meaningful diagnostic modality in the management of various cancers, with accuracy in the detection of recurrence and treatment response evaluation in patients with CRC and other types of tumors, such as s ovarian cancer, and Hodgkin and non-Hodgkin lymphomas (15)(16)(17). It has been shown that PET has higher sensitivity as compared with CT in the detection of abdominal and extra-abdominal metastatic sites (17).…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT has been proven to be a meaningful diagnostic modality in the management of various cancers, with accuracy in the detection of recurrence and treatment response evaluation in patients with CRC and other types of tumors, such as s ovarian cancer, and Hodgkin and non-Hodgkin lymphomas (15)(16)(17). It has been shown that PET has higher sensitivity as compared with CT in the detection of abdominal and extra-abdominal metastatic sites (17).…”
Section: Discussionmentioning
confidence: 99%
“…En los pacientes tratados de una neoplasia colorectal, con la sospecha de recurrencia basada en la elevación sérica del antígeno carcinoembrionario, el cambio de manejo terapéutico provocado por la PET es del 39% y no difiere de los resultados previamente obtenidos por Vitola 20 (25%), Lai 21 (29%), Delbeke 22 (33%), Ogunbiyi 23 (44%) o Valk 24 (31%). Este cambio de actitud terapéutica se explica por una una mayor sensibilidad de la PET con respecto a la TAC en la valoración de la infiltración tumoral del abdomen, la pelvis y el retroperitoneo, así como por su capacidad de detectar enfermedad tumoral en localizaciones pocos habituales (mediastino, hueso y glándulas suprarrenales) 24 .…”
Section: Discussionunclassified
“…The residual pelvic soft tissue abnormalities frequently seen in the tumor bed region after therapy usually complicate the detection of local recurrence by the conventional imaging techniques 1314. Abnormal 18 F-FDG activity in a residual pelvic soft tissue lesion after 6 months from the completion of radiotherapy most likely represents tumor recurrence, and accuracy and positive predictive value (PPV) are even higher after 12 months 111516.…”
Section: Methodsmentioning
confidence: 99%